2008
DOI: 10.1122/1.2837525
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic effects on drop deformation in a converging pipe flow

Abstract: This paper reports finite-element simulations of drop deformation in converging flows in an axisymmetric conical geometry. The moving interface is captured using a diffuse-interface model and accurate interfacial resolution is ensured by adaptive refinement of the grid. We have explored the effects of viscoelasticity on drop deformation when either the drop or the matrix is a Giesekus fluid. Contrary to the popular belief that viscoelasticity in the drop hinders deformation and that in the matrix enhances defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…G can be likened to the capillary number in drop dynamics (e.g., Zhou et al, 2008). We can also define two ratios between the moduli:…”
Section: Results and Analysismentioning
confidence: 99%
“…G can be likened to the capillary number in drop dynamics (e.g., Zhou et al, 2008). We can also define two ratios between the moduli:…”
Section: Results and Analysismentioning
confidence: 99%
“…As with previous studies ( [14], [35], [15,36], [18]) Oldroyd B model is chosen as a simple constitutive model despite its shortcomings. Recent numerical simulations [8,37] have incorporated a small Giessekus parameter to the Oldroyd B model used by the same investigators previously, but the results were found not to be affected by it. In view of this we prefer not to incorporate any additional parameter; the simulation results seem to be free of the numerical difficulties within the range of Deborah numbers studied.…”
Section: Introductionmentioning
confidence: 92%
“…They report a non-monotonic change in deformation for a viscoelastic droplet in a viscous matrix while the reversed case was seen to increase droplet deformation. Yue et al [39][40][41][42][43][44] performed various numerical calculations based on a diffuse-interface formulation and the Oldroyd-B constitutive equation for the non-Newtonian phase [40]. Such analysis was then extended by Aggarwal & Sarkar [21,22] using a 3D front-tracking finite difference numerical method.…”
Section: Introductionmentioning
confidence: 99%